Artificial Intelligence System for Face Detection to Identify Passenger Identity at the Airport - Solikin, Akhmad; rochman, sagita; Widiarto, Budi (Universitas PGRI Adi Buana Surabaya, 2025)
Facial biometric technology is widely used in various fields such as bank security, border crossings, airport check-in, home surveillance, remote meetings in offices, prisons, and factories. This makes facial recognition an important field to study and develop. In countries like the United States and Germany, trials have begun for the implementation of Face Recognition technology in airport areas. This technology is used for airport check-in systems to address the issue of long queues, especially during holiday seasons, which is a common occurrence in airports worldwide. Although online check-in methods already exist, they still do not resolve this issue. Unfortunately, this technology has not yet been implemented or discussed for application in Indonesian airports. Therefore, the researchers intend to conduct a study on this technology to ensure that Indonesia does not fall behind other countries in facial detection technology. Based on the test results of the developed system, it can be concluded that the facial detection system is quite effective in identifying faces, but there are some limitations, such as lighting and facial accessories. The system works optimally at light intensities ranging from 806 lumens to 161 lumens, and if the person to be detected is wearing a mask or sunglasses, the system will not be able to recognize the face.